(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The strengthening of the tradition of using punctuation marks according to the author’s style made it possible to use punctuation marks in a way that does not obey the norm. Author’s punctuation - the occasional usage of punctuation marks according to the author’s style, although observed since the 18th century, reached its final stage of development at the end of the last century. These traditions entered the Uzbek script through the punctuational calka in the process of translation of artistic and scientific works written in English and Russian into Uzbek language.